2016
DOI: 10.1021/acsmacrolett.5b00855
|View full text |Cite
|
Sign up to set email alerts
|

Is Molecular Weight or Degree of Polymerization a Better Descriptor of Ultrasound-Induced Mechanochemical Transduction?

Abstract: A detailed understanding of the fundamental processes that govern mechanical transduction in covalent polymer mechanochemistry is essential to advance innovation in this field. In contrast to progress in the development of new mechanophores, the influence of polymer structure and composition on mechanochemical activity has received relatively little attention. In order to address this gap in knowledge, a continuous flow system with synchronous UV−vis absorption capabilities was designed to quantify the ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
121
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(133 citation statements)
references
References 30 publications
10
121
1
1
Order By: Relevance
“…As previously demonstrated in Titin, [12,13] the scission of sacrificial bonds absorb applied mechanical stress without polymer fragmentation. Assuming that the stress transduced to the polymer chain is proportional to the DP, [27,28] less energy is consumed in unfolding the polymer before as acrificial bond is stretched, explaining the higher rate of mechanochemical scission events.Furthermore, intramolecular collapse inhibits the unfolding of the polymer under solvodynamic shear, reducing the maximum stress in polymer chains,b ased on the models proposed by Odell and Keller. [3,29,35] This reduction in peak stress explains the reduction in mechanochemical rates at higher cross-link densities,inw hich as teeper reduction of Rh is observed.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…As previously demonstrated in Titin, [12,13] the scission of sacrificial bonds absorb applied mechanical stress without polymer fragmentation. Assuming that the stress transduced to the polymer chain is proportional to the DP, [27,28] less energy is consumed in unfolding the polymer before as acrificial bond is stretched, explaining the higher rate of mechanochemical scission events.Furthermore, intramolecular collapse inhibits the unfolding of the polymer under solvodynamic shear, reducing the maximum stress in polymer chains,b ased on the models proposed by Odell and Keller. [3,29,35] This reduction in peak stress explains the reduction in mechanochemical rates at higher cross-link densities,inw hich as teeper reduction of Rh is observed.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…All SCPNs,a sw ell as the linear precursor,p resent the same DP with the only distinction being the amount of crosslinker.Importantly,ithasbeen recently shown that DP is the key parameter that defines the rate of mechanochemical reactions,a nd therefore all samples should present the same degradation rate, [27,28] unless,a sw ep ropose,t here is as tructural effect in the way the stress is transmitted to the polymer or dissipated as aconsequence of the intramolecular collapse.…”
mentioning
confidence: 99%
“…The high molecular weight peak situated at around 200 kDa decreases rapidly and adds to the original low molecular weight peak of PMA-2 at 100 kDa. 34,35 Indeed, from the 1 H-NMR spectra it becomes clear that neither thermal dissociation nor irradiation with ultrasound of 1 lead to the formation of TPI or other considerable degradation of the HABI-moiety during the monitored time span. 1 H-NMR measurements clearly confirm that scission occurs mostly at the HABI-moiety (Fig.…”
mentioning
confidence: 99%
“…[24] TheN MR and GPC data suggest that ring-opening olefination by sonication was concurrent with chain scission, as expected from the sonication of macromolecules. As expected, sonication of the low-molecularweight control VA -TES polymers did not result in any observable olefination or chain scission, since they are below the required degree of polymerization for sonicationinduced cleavage.…”
Section: Angewandte Chemiementioning
confidence: 59%
“…As expected, sonication of the low-molecularweight control VA -TES polymers did not result in any observable olefination or chain scission, since they are below the required degree of polymerization for sonicationinduced cleavage. [24] TheN MR and GPC data suggest that ring-opening olefination by sonication was concurrent with chain scission, as expected from the sonication of macromolecules. [25] A representative series of GPC traces taken during sonication of VA -TES are shown in Figure 3(top).…”
Section: Angewandte Chemiementioning
confidence: 59%